Beyond the Wave, the Sea: Re-assessing the Impact of the Economic Crisis on Southern Europe's Populist Upsurge - Arthur Borriello (University of Groningen Press, 2021)
The paper re-assesses the relation between the economic crisis and the rise of populist parties in the South of Europe. It argues that the former did not cause the latter directly, but rather played out as a catalyst of previously existing trends, i.e. the erosion of party democracy and the disintermediation of Western societies. It combines several theoretical approaches to advance an explanatory model that replaces the relation between crisis and populism – conceived of as political, performative and discursively mediated – within its structural pre-conditions. By doing so, it aims at providing a synthetic and steady explanation of the contemporary rise of populism in Southern Europe and beyond.